Mapped in Bangladesh (MiB) Rapid Survey Phase 2: status of the export oriented RMG factories in Bangladesh during Covid-19 pandemic - Islam, MD. Faizul; Shajahan, Sadril; Chowdhury, Fahim S (Mapped in Bangladesh (MiB) project of Centre for Entrepreneurship Development (CED), Brac University, 2021)
To address the operational status of the export-oriented Ready-Made Garment (RMG) factories in Bangladesh during the ongoing Covid-19 pandemic, the Mapped in Bangladesh (MiB) project of Centre for Entrepreneurship Development (CED) of Brac University (BracU) has been undertaking a series of Rapid Survey(s). The Phase 1 was conducted during the 1 st week of May 2020 and a research brief was published on 1 June 2020, along with the development of Covid-19 RMG Map showing which factories are producing face mask and personal protective equipment (PPE), along with the status of their deployed workers’ number during the pandemic. The data for the Phase 2 of the Rapid Survey was collected during 15-23 June 2020. The major data points for the Rapid Survey Phase 2 are: factory name, operational status of factories, expectation of factories for continuing operation after June 2020, total number of workers deployed in factories at present; percentage of total capacity1 utilized for operation; whether factories are producing face mask, PPE and/or regular products; the profitability mode (with or without profit margin), the market (domestic/export), and the brands that the face masks and PPEs are being produced for; whether the factories arranged trainings or briefings about Cocid-19 awareness for their workers; and the measures the factories have taken to prevent their workers and visitors from being infected by the virus.